2015
DOI: 10.1016/j.renene.2015.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the offshore wind resources of the State of Ceará in Brazil

Abstract: a b s t r a c tThe onshore wind power is consolidated; the challenge is to reach the same level of maturity for offshore exploitation. Brazil has no offshore wind power plants and there are few studies in this direction. This paper aims to estimate the offshore wind resources in the State of Cear a, in Brazil. The investigation uses a mesoscale atmospheric computer model, the Regional Atmospheric Modeling System (RAMS), with horizontal resolution of 2 km, which estimates the offshore average wind speed, averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 11 publications
0
10
0
6
Order By: Relevance
“…In the long term, the transmission infrastructure must be restructured to meet changing requirements and eventually yield an efficient integration of renewable energy generation [42,43]. Although Brazil account with the highest potential of wind power [16,44,45], from our results found that coordination of energy policy is a crucial aspect for obtaining the reduction of asynchrony on the supply chain.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In the long term, the transmission infrastructure must be restructured to meet changing requirements and eventually yield an efficient integration of renewable energy generation [42,43]. Although Brazil account with the highest potential of wind power [16,44,45], from our results found that coordination of energy policy is a crucial aspect for obtaining the reduction of asynchrony on the supply chain.…”
Section: Resultsmentioning
confidence: 81%
“…Given the role of wind industry for the Brazilian electricity market, this paper surveys unsynchronised energy policy related with time-delays of Int J Elec & Comp Eng ISSN: 2088-8708  construction of transmission lines and recent changes of the auctions' policy in practice that affects the development of wind-power supply chain. Despite an increase of auctions for transmission lines in the last year, Brazilian electricity market faces drawback related with the delays to build extensive transmission network for energy supply [7], [16][17][18]. Currently, reduction in auctions in the short term, as present in Figure 1, and the more considerable variability of electricity prices in the medium and long term represents a significant challenge for wind industry investments.…”
Section: Introductionmentioning
confidence: 99%
“…If we want to advance wind power to new frontiers, as Lima et al (2015) indicate in studies that estimate the production of offshore wind energy in coastal Ceará, we should develop better forms of planning relating to siting wind farms and the management of benefits generated by wind power.…”
Section: Final Considerationsmentioning
confidence: 99%
“…A wide variety of studies have evaluated wind resource potential in regions such as offshore of Ceará, Brazil [5], onshore in the Arabian Peninsula [6] and the entire United States, both onshore and offshore [7]. Further studies have integrated wind speed with turbine power curves to create generation profiles offshore of California (not including the Humboldt Call Area) [8,9], Oregon [10], the east coast of the United States [11], northern Spain [12], the Persian Gulf [13], and the gulf of Thailand [14], and onshore in Rafha, Saudi Arabia [15], South Africa [16], and Algeria [17].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have integrated wind speed with turbine power curves to create generation profiles offshore of California (not including the Humboldt Call Area) [8,9], Oregon [10], the east coast of the United States [11], northern Spain [12], the Persian Gulf [13], and the gulf of Thailand [14], and onshore in Rafha, Saudi Arabia [15], South Africa [16], and Algeria [17]. Some of these studies rely on descriptive statistics of measured wind speed [16,17] or modeled wind speed (generally based on relatively sparse measurement data) [9,13], and some use the measured [15] or (most commonly) modeled data directly [5][6][7][8][10][11][12]14,18].…”
Section: Introductionmentioning
confidence: 99%